A Case of In-Bore Transperineal MRI-Guided Prostate Biopsy of a Patient with Ileal Pouch-Anal Anastomosis - Michael Kongnyuy; Thomas Frye; Arvin K. George; Amichai Kilchevsky; Amogh Iyer; Meet Kadakia; Akhil Muthigi; Baris Turkbey; Brad J. Wood; Peter A. Pinto (Case Reports in Urology)
Ulcerative colitis (UC) is an inflammatory disease that specifically affects the colon. Ulcerative colitis is primarily treated medically and refractory disease is treated with proctocolectomy and ileal pouch-anal anastomosis (IPAA). Gastroenterologists advise against digital rectal exams, pelvic radiation therapy, and transrectal ultrasound (TRUS) biopsies of the prostates of ileal pouch-anal anastomosis patients. Any form of pouch manipulation can lead to severe bleeding, inflammation, and pain. Urologists are therefore faced with the challenge of doing a prostate biopsy without a transrectal ultrasound. We report the rare case of a patient with an ileal pouch-anal anastomosis who underwent in-bore transperineal MRI-guided biopsy of the prostate.